PRINCIPLES OF TEAMMAKING AS THE EFFECTIVE INSTRUMENT OF MANAGEMENT - Mazur, Volodymyr; Мазур, В.С. (Scientific Journal Virtus Issue # 15, July, 2017. – P. 251-253, 2017)
The article deals with an active mechanism of creating an effective managerial team under modern economic conditions; principles, methods and ways of work in team; the possibility to work for getting a result in the light of personal qualities of each representative of a team taking into account their psychological aspects.
ПРИНЦИПЫ СОЗДАНИЯ КОМАНДЫ – ЭФФЕКТИВНЫЙ ИНСТРУМЕНТ УПРАВЛЕНИЯ
Keywords: team; leader; human resources; psychological factors; work principle; intensive work